Serum microRNA-17 functions as a prognostic biomarker in osteosarcoma - Li, Shuai (Oncol Lett, 2016)
MicroRNAs (miRNAs/miRs) are a class of small noncoding RNA molecules that have important roles in regulating the expression of target genes associated with the development and progression of cancer. The majority of miRNAs are expressed in a highly tissue- and region-specific manner, and released into the bloodstream as a consequences of different diseases. Furthermore, altered levels of miRNAs have been observed in several diseases, including cancer. In the present study, reverse transcription-quantitative polymerase chain reaction (RT-qPCR) demonstrated that circulating miR-17 levels were significantly upregulated in patients with osteosarcoma (OS) compared with healthy subjects. RT-qPCR also revealed that high levels of circulating miR-17 expression were inversely correlated with phosphatase and tensin homolog expression, which was identified as a target gene of miR-17 in OS tissues. Furthermore, the overall survival of patients with OS was shorter in those with high miR-17 expression compared with moderate and low expression. Taken together, these findings indicate that miR-17 may function as a useful diagnostic and prognosis biomarker or therapeutic target of OS.